Carbamazepine Induced Thrombocytopenia - Ruhi Kumar; Sridhar Chivukula; Goutham Reddy Katukur; U K Chandrasekhar; K N Shivashankar (Journal of Clinical and Diagnostic Research, 2017)
Antiepileptic Drugs (AEDs) are commonly associated with haematological disorders, including anaemia, thrombocytopenia, neutropenia and even bone marrow failure. Fatal disorders like aplastic anaemia are uncommon. On exploring through the literature, older AEDs are more associated with haematological alterations than newer AEDs, and careful monitoring is warranted especially with phenytoin, carbamazepine and valproate. The exact cause of these alterations is not established, though immune mechanisms and pharmacology of individual drugs are the proposed mechanisms, a further research along this path is underway. Of worth mentioning here, this predilection of older AEDs towards haematological disorders is pronounced in children compared to adults. We present here a case of congenital heart disease with history of brain abscess and seizures, on carbamazepine who presented to our hospital with toothache. Routine screening prior to tooth extraction revealed thrombocytopenia. Further evaluation revealed the association of carbamazepine and thrombocytopenia, which mandated discontinuation of drug and switching patient to alternative AED.